Inhibition of the amino‐acid transporter LAT1 demonstrates anti‐neoplastic activity in medulloblastoma. Issue 4 (19th February 2019) - Cormerais, Yann; Pagnuzzi‐Boncompagni, Marina; Schrötter, Sandra; Giuliano, Sandy; Tambutté, Eric; Endou, Hitoshi; Wempe, Michael F.; Pagès, Gilles; Pouysségur, Jacques; Picco, Vincent
Abstract: Most cases of medulloblastoma (MB) occur in young children. While the overall survival rate can be relatively high, current treatments combining surgery, chemo‐ and radiotherapy are very destructive for patient development and quality of life. Moreover, aggressive forms and recurrences of MB cannot be controlled by classical therapies. Therefore, new therapeutic approaches yielding good efficacy and low toxicity for healthy tissues are required to improve patient outcome. Cancer cells sustain their proliferation by optimizing their nutrient uptake capacities. The L‐type amino acid transporter 1 (LAT1) is an essential amino acid carrier overexpressed in aggressive human cancers that was described as a potential therapeutic target. In this study, we investigated the therapeutic potential of JPH203, a LAT1‐specific pharmacological inhibitor, on two independent MB cell lines belonging to subgroups 3 (HD‐MB03) and Shh (DAOY). We show that while displaying low toxicity towards normal cerebral cells, JPH203 disrupts AA homeostasis, mTORC1 activity, proliferation and survival in MB cells. Moreover, we demonstrate that a long‐term treatment with JPH203 does not lead to resistance in MB cells. Therefore, this study suggests that targeting LAT1 with JPH203 is a promising therapeutic approach for MB treatment.